Analysis of mathematical reasoning ability of class VIII in view of Bobbi DePorter's learning style - Ariana Dwi Hidayati; Zuida Ratih Hendrastuti; Yesi Franita (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to analyze student mathematical reasonings abilities in terms of learnings style according to Bobbi DePorter. This research is descriptive qualitative research. The subject of this studies were students of class VIII A and VIII F at SMPN 13 Magelang. The instruments used include learnings styles questionnaires, test questions with indicator of mathematical reasonings abilities, interviews, and documentation. The result of the study showed that from 58 students there were 30 students with visual learning styles, 15 students with auditory learning styles, and 13 students with kinesthetic learnings style. Class VIII students at SMPN 13 Magelang tend to have a visuals learnings styles. The mathematical reasoning abilities of student with visuals learnings style is classified at the moderate level with a percentage of 61.8%, Auditory learning style is classified as medium level with a percentage of 69.3%, and kinesthetic learning style is classifieds as low level with a percentage of 54.7%. So it can be concludes that the mathematical reasonings abilities of class VIII student at SMPN 13 Magelang is classified as moderate.